RESEARCH ON CRASHWORTHINESS OF BIONIC PENTACLE THIN-WALLED STRUCTURE INSPIRED BY CARAMBOLA - SUN YuZhou; YANG ZhuoRan; XIA Yan; JIANG Han (Jixie qiangdu)
Thin-walled energy absorber plays an important role in aerospace, transportation and other fields. Inspired by carambola fruit with excellent crashworthiness, the bio-inspired pentacle thin-walled structure was designed. The deformation and energy absorption mechanism of the struct were analyzed by finite element simulation, experiment and theory. The influence of cross-section shapes and geometric parameters on the energy absorption characteristies were discussed. Investigations were carried out on the optimization effect of hierarchy and stiffener on crashworthiness. The results show that the bio-inspired pentacle thin-walled structure has regular progressive folding deformation mechanism. The crashworthiness properties of pentacle thin-walledstructure, such as specific energy absorption and crushing force efficiency, are significantly better than that of thin-walled structures with common sections, showing good engineering application potential.